Slug length for high viscosity oil-gas flow in horizontal pipes: experiments and prediction - Baba, Yahaya D.; Aliyu, Aliyu M.; Archibong-Eso, Archibong; Abdulkadir, Mukhtar; Lao, Liyun; Yeung, Hoi (Elsevier, 2018)
An experimental investigation was carried out on the effects of high liquid viscosities on slug length in a 0.0762-m ID horizontal pipe using air-water and air-oil systems with nominal viscosities ranging from 1.0 to 5.5 Pa s. The measurements of slug length were carried out using two fast sampling gamma densitometers with a sampling frequency of 250 Hz. The results obtained show that liquid viscosity has a significant effect on slug length. An assessment of existing prediction models and correlations in the literature was carried out and statistical analysis against the present data revealed some discrepancies, which can be attributed to fluid properties in particular, low viscous oil data used in their derivation Hence, a new high viscous oil data presented here from which we derive a new slug length correlation was derived using dimensional analysis. The proposed correlation will improve prediction of slug length as well as provide a closure relationship for use in flow simulations involving heavy oil. This is important since most current fields produce highly viscous oil with some reaching 10 Pa s.
Keywords: High viscosity oil; Gamma densitometer; Slug lengthTranslational velocity; Two phase flow